2020
DOI: 10.1177/1758835920937612
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of PD-1/PD-L1 blockade monotherapy in clinical trials

Abstract: Background: Inhibitors targeting programmed cell death 1 (PD-1) and programmed death-ligand 1 (PD-L1) have unprecedented effects in cancer treatment. However, the objective response rates (ORRs), progression-free survival (PFS), and overall survival (OS) of PD-1/PD-L1 blockade monotherapy have not been systematically evaluated. Methods: We searched Embase, PubMed, and Cochrane database from inception to July 2019 for prospective clinical trials on single-agent PD-1/PD-L1 antibodies (avelumab, atezolizumab, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 198 publications
(184 reference statements)
2
76
0
1
Order By: Relevance
“…Anti-PD(L)1 immune checkpoint inhibitors (ICI) singly or in combination with anti-CTLA-4 or other agents are approved across multiple indications in sixteen separate diseases including a histology-agnostic indication in patients with microsatellite instability-high (MSI-H) or mismatch repair deficient (dMMR) solid tumors. 1,2 The hallmark of ICI therapy is the durability of responses in a subset of patients as evidenced by progression-free survival (PFS) rates of 21-29% in melanoma and 22% in non-small cell lung cancer (NSCLC) with anti-PD(L)1 singly; [3][4][5][6][7] and up to 36% with anti-PD-1/anti-CTLA-4 dual ICI in melanoma. 8 However, the majority of patients do relapse and the question of how to improve outcomes in these patients remains a vexing problem for the field.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-PD(L)1 immune checkpoint inhibitors (ICI) singly or in combination with anti-CTLA-4 or other agents are approved across multiple indications in sixteen separate diseases including a histology-agnostic indication in patients with microsatellite instability-high (MSI-H) or mismatch repair deficient (dMMR) solid tumors. 1,2 The hallmark of ICI therapy is the durability of responses in a subset of patients as evidenced by progression-free survival (PFS) rates of 21-29% in melanoma and 22% in non-small cell lung cancer (NSCLC) with anti-PD(L)1 singly; [3][4][5][6][7] and up to 36% with anti-PD-1/anti-CTLA-4 dual ICI in melanoma. 8 However, the majority of patients do relapse and the question of how to improve outcomes in these patients remains a vexing problem for the field.…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analyses of the efficacy of antibodies targeting PDCD1/CD274 as monotherapy [ 7 , 8 ] found that this treatment is associated with more tumor responses and increased overall survival (OS) compared to conventional therapy. Although there are some patients who show long-term complete responses [ 9 , 10 ], the average response rate is 20% with significant differences across different tumor types [ 8 ]. It is of significant interest to identify the minority of patients who will benefit from immune checkpoint blockade to better direct this therapy and avoid the (often immune-mediated) adverse events [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint blockade of PD-1/PD-L1 is being widely tested against different cancer types, with various levels of success [ 39 ]. Despite the presence of immune infiltrates in patients with ovarian cancer, PD-1/PD-L1 blockade has shown limited effectiveness in clinical trials with only a modest 9–15% response rate [ 15 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%